Предмет: Математика,
автор: gjdijshsjs18
Упростить выражение
2(x-3) во второй степени + 12x
Ответы
Автор ответа:
0
2(2х-6х+6)+12х=4х-12х+12+12х= 16х
4х-12х+12+12х(объяснение) = -12х и +12х взаимно-уничтожай, 4х + 12х = 16х
Ответ:16х
надеюсь помогла)
4х-12х+12+12х(объяснение) = -12х и +12х взаимно-уничтожай, 4х + 12х = 16х
Ответ:16х
надеюсь помогла)
Автор ответа:
0
формулы надо знать и все легко будет)
Автор ответа:
0
Большое спасибо, очень помогли!)
Похожие вопросы
Предмет: Биология,
автор: veronikagorbatenko37
Предмет: Литература,
автор: GubaevaKamila
Предмет: Математика,
автор: ailin88
Предмет: Алгебра,
автор: faridbadalov97